The role of social representations in criticizing the medical perception of health and disease - Anfeekh, Mohammed Ahmed (Journal of Humanities & Social Sciences, 2019)
This article is intended to reveal that the topics concerned with health and disease cannot be a pure medical speech topic , because they are not only two physical happens , but they are built socially and culturally as well. thus , the sociologists have produced another speech , which , on the one hand , was regarded as parallel or marginal to medical speech , on the other hand , it was considered as competitive to it. the sociologists have relied on multiple entries so as to construct the social reality related to this topic , the social representations entry is among them , this entry has showed that expressing the state of health and disease is no longer presented by body language , as the doctors believe , but by the language of society and culture. therefore , it is compulsory to dispense with medical centralization and to adapt a various and extrovert vision. moreover , the issue of health should become a social matter that involves medical , political , economical , lawful , and cultural trends.